Advancing approach and toolbox in optimization of chloroplast genetic transformation technology - Yu-xin LIU; Fan LI; Liang GAO; Zhang-li TU; Fei ZHOU; Yong-jun LIN (Journal of Integrative Agriculture, 2023)
Chloroplast is a discrete, highly structured, and semi-autonomous cellular organelle. The small genome of chloroplast makes it an up-and-coming platform for synthetic biology. As a special means of synthetic biology, chloroplast genetic engineering shows excellent potential in reconstructing various sophisticated metabolic pathways within the plants for specific purposes, such as improving crop photosynthetic capacity, enhancing plant stress resistance, and synthesizing new drugs and vaccines. However, many plant species exhibit limited efficiency or inability in chloroplast genetic transformation. Hence, new transformation technologies and tools are being constantly developed. In order to further expand and facilitate the application of chloroplast genetic engineering, this review summarizes the new technologies in chloroplast genetic transformation in recent years and discusses the choice of appropriate synthetic biological elements for the construction of efficient chloroplast transformation vectors.